2010
DOI: 10.1038/ajh.2009.210
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Blood Pressure Control and Hospitalization Risk to Medication Adherence Among Patients With Hypertension in Taiwan

Abstract: Our observation study clearly indicates that lower medication adherence is associated with poor BP control and higher risk of CVD and all-cause hospitalization in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 27 publications
4
66
0
2
Order By: Relevance
“…Our study provides further support for previous findings 12,13,31 about the association of adherence to antihypertensive medication on hospitalization for CVD. Compared with those patients with good medication adherence, patients with poor adherence were 1.42× more likely to require hospitalization for AMI.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study provides further support for previous findings 12,13,31 about the association of adherence to antihypertensive medication on hospitalization for CVD. Compared with those patients with good medication adherence, patients with poor adherence were 1.42× more likely to require hospitalization for AMI.…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis reported that patients adherent to antihypertensive medications showed better blood pressure control, compared with those who were nonadherent (odds ratio, 3.44; 95% confidence interval [CI], 1.60-7.37). 11 Evidence is mounting that patients who show poor adherence to antihypertensive medication have a higher risk of adverse outcomes, including allcause hospitalization and CVD hospitalization, 12,13 and they have higher healthcare costs 14 compared with patients with good adherence. 12,13,15 A recent cohort study 15 reported that a good-adherence group had a significantly lower incidence of acute cardiovascular events, compared with a group with poor adherence to antihypertension medication (hazard ratio [HR], 0.62; 95% CI, 0.40-0.96).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25] Our secondary outcome was time to first allcause hospitalization/ED visit during the 12 months after the first year of treatment, given that medication non-adherence may manifest as numerous different adverse outcomes (e.g., falls) and, therefore, increase the risk of all-cause hospitalizations/ED visits. 3,[26][27][28][29] Exposures: Adherence to Oral Hypoglycemics…”
Section: Outcome Measuresmentioning
confidence: 99%
“…[8][9][10] Consistent adherence to cardiovascular and/or antidiabetic medication therapy, on the other hand, is associated with better healthrelated outcomes. 11,12 Reducing Cardiovascular Medication Complexity in a German University Hospital: Effects of a Structured Pharmaceutical Management Intervention on Adherence the dose titration is completed after discharge; or the brand is switched for financial reasons. However, careful optimization of medication complexity might be short lived when primary care providers (PCPs) are not informed about the background of the treatment modifications.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%